Assertive training for social interaction with the opposite sex in women from a self-help center from Lima - Monteagudo Prado, María Ysabel (2018)
The research presents the results of the effect of assertive training on social interaction with the opposite sex in 20 women of a self-help center in Lima. Assertive training was applied through modeling and role play techniques, cognitive restructuring technique, self-instructions, relaxation and support techniques such as housework. The methodology is causal type, and to measure the social interaction variable in its behavioral and cognitive dimensions, besides, an instrument, The emotion matching list of Monteagudo (2010) were applied. We worked with economically independent professional singles with negative experience of relation with negative thoughts and beliefs towards the male. The women were able to increase their social interaction behavior with the opposite sex, having a change of 80% in the measurements before and after the intervention. The behaviors were also measured in the natural environments, observing the changes in the interaction.